पात्रविधानका कोणबाट ’चन्द्रवदन’ कथाको अध्ययन [Study of ’Chandravadan’ story from the angle of characterization] - प्रभात Prabhat रमेश Ramesh (BMC Journal of Scientific Research, 2020)
Available with full text.